Enhancement, suppression of the emission and the energy transfer by using a graphene subwavelength wire - Cuevas, Mauro (2018)
The present work focuses on theoretically research on the spontaneous emission and the energy transfer process between two single optical emitters placed close to a graphene coated wire. The localized surface plasmons (LSPs) supported by the structure provide decay channels which lead to an enhancement of the emission and radiation decay rates as well as an improvement in the energy transfer between two dipole emitters. Modifications resulting from varying the orientation of dipole moments in these quantities are shown. We find that the radiation and the energy transfer efficiencies can be largely reduced at a specific frequency depending on the emitter location. By dynamically tuning the chemical potential of graphene coating, the spectral region where the dipole–field interaction is enhanced can be chosen over a wide range.